2012
DOI: 10.1666/10026.1
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and extinction in Ordovician–Silurian brachiopods, Cincinnati Arch, Ohio and Kentucky

Abstract: A basic hypothesis in extinction theory predicts that more abundant taxa have an evolutionary advantage over less abundant taxa, which should manifest as increased survivorship during major extinction events and longer fossil-record durations. Despite this, various paleontologic studies have found conflicting patterns, indicating a more complex relationship between abundance and extinction in the geologic past. This study tests the relationship between abundance and extinction among brachiopod genera within se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(93 reference statements)
2
5
0
Order By: Relevance
“…Yet our results are in accord with other analyses of the fossil record that have found no association between abundance and extinction risk [24], or a negative association that was due entirely to covariation between abundance and geographic range size [3]. More broadly, positive [49], negative [4,50] and non-monotonic [23] relationships have all been reported in palaeontological studies. This degree of heterogeneity contrasts markedly with the consistent negative association between geographic range size and extinction risk, and strongly suggests that taxa observed at low abundance in the fossil record had population sizes that were considerably greater than the minimum size below which the effects of demographic stochasticity become critical [51,52] and/or possessed traits that allowed them to counteract the problems of reproduction and recruitment at low densities.…”
Section: Resultssupporting
confidence: 92%
“…Yet our results are in accord with other analyses of the fossil record that have found no association between abundance and extinction risk [24], or a negative association that was due entirely to covariation between abundance and geographic range size [3]. More broadly, positive [49], negative [4,50] and non-monotonic [23] relationships have all been reported in palaeontological studies. This degree of heterogeneity contrasts markedly with the consistent negative association between geographic range size and extinction risk, and strongly suggests that taxa observed at low abundance in the fossil record had population sizes that were considerably greater than the minimum size below which the effects of demographic stochasticity become critical [51,52] and/or possessed traits that allowed them to counteract the problems of reproduction and recruitment at low densities.…”
Section: Resultssupporting
confidence: 92%
“…The results of the logistic regression analyses show that there is no statistically significant association between average local conodont abundance and extinction risk during the Ireviken event. This pattern is congruent with the results of previous paleobiological macroevolutionary studies, which largely revealed relatively weak to non-existent [ 60 , 61 , 62 ] (including cases of mass extinction [ 63 ]) and occasionally nonlinear and context-dependent influences [ 64 , 65 ] of local abundance on extinction probability. However, it is possible that these patterns reflect weak statistical testing methods, as small abundance effect sizes (and other statistically insignificant factors) on risk were confounded by small sample sizes used in the analyses [ 66 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ordovician data were obtained from Patzkowsky and and Silurian data came from Zaffos and Holland (2012). Ordo-FIGURE 1.…”
Section: Methodsmentioning
confidence: 99%